SOCIAL MEDIA AND POLITICAL PARTICIPATION IN INDONESIA: RESTRICTIONS ACCESS AT ANNOUNCEMENT RESULTS OF 2019 PRESIDENTIAL ELECTION - Palupi Anggraheni; Novi Tri Setyowati; Harry Harry (ASPIKOM Jabodetabek Region, 2021)
The penetration of technology as a driving force for movement and a hub between humans and machines fundamentally shifts the way humans think, interact and move. One of the benchmarks for highly increasing digital activity in Indonesia nowadays is the massive use of the internet, including social media. On the other hand, the increasing use of social media also becomes a challenge in popularizing the political participation of the public. One example of a case that illustrates this phenomenon is the limitation of access to social media in the 2019 Presidential Election (Pilpres). The public experienced difficulties in accessing social media, after the announcement of the vote recapitulation of the 2019 Presidential Election. It can be seen as a challenge to the freedom of speech in Indonesia or the other hand could be seen as a preventive measure to prevent the escalation of riots. As library research, this paper discusses in more detail the relationship between the role of social media, and government policies, in the framework of political participation. The concept of social media’s role in political participation, especially in creating online public opinion by Robles-Moralez & Cordoba-Hernandez, is used to help analyze social media as a catalyst in increasing public engagement in elections. It can be concluded that social media plays a role as “dismediation” agent and disrupt power plays between conventional elite media in delivering information from government to citizen vice versa.